Makna Mengampuni Tanpa Batas Menurut Matius 18 : 21 – 35 dan Implikasinya Bagi Kekristenan Masa Kini - Benny Christian Hutabarat; Rogate Artaida Tiarasi Gultom; Ibelala Gea (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
Forgiveness is a word that is often heard, but is difficult to implement. Giving forgiveness is not based on the size of the mistake committed, but all mistakes must be forgiven. You also need to know that giving forgiveness is not just to forget, but because forgiveness is an obligation for everyone. By giving forgiveness, what happens is peace. Forgiveness is not a verb that must be questioned, but forgiveness requires intention and must be done.This article uses qualitative methods and a literary approach with descriptive analysis of the text of Matthew 18: 21 – 35, in order to explain the research object precisely. Therefore, the aim of the research is to explain the correct understanding of the meaning of Forgiving Without Limits.